1991
DOI: 10.1152/ajpcell.1991.261.3.c530
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy of isolated adult feline heart cells following beta-adrenergic-induced beating

Abstract: Catecholamine-induced beating and myocardial hypertrophy were evaluated in isolated adult feline cardiomyocytes maintained in culture for up to 30 days. Adult feline cardiomyocytes were used in this study because they displayed several unique characteristics that facilitated assessment of factors regulating cardiomyocyte hypertrophy in vitro. These characteristics included the following. 1) A single heart provides a high yield of 20-40 x 10(6) calcium-tolerant rod-shaped myocytes. 2) In culture, isolated adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…It has been reported that cardiac hypertrophy characterized by an increase in cell size was induced by catecholamines (Simpson et al 1982;Simpson and McGrath 1983;Simpson 1985;Tang et al 1987;Clark et al 1991). Therefore, to confirm whether cellular hypertrophy occurred in ARCs used in this experiment, ARCs were exposed to 0.1, 1.0 or 2.0 µM l-norepinephrine bitartrate (NE, Wako, Japan) for 7 days (from days 6 to 13 in culture).…”
Section: Resultsmentioning
confidence: 88%
“…It has been reported that cardiac hypertrophy characterized by an increase in cell size was induced by catecholamines (Simpson et al 1982;Simpson and McGrath 1983;Simpson 1985;Tang et al 1987;Clark et al 1991). Therefore, to confirm whether cellular hypertrophy occurred in ARCs used in this experiment, ARCs were exposed to 0.1, 1.0 or 2.0 µM l-norepinephrine bitartrate (NE, Wako, Japan) for 7 days (from days 6 to 13 in culture).…”
Section: Resultsmentioning
confidence: 88%
“…27 Data were normalized to the relative amount of protein-bound radioactivity observed in unstretched cultures of spontaneously beating myocytes and were pooled from 4 experiments. Two-way ANOVA was used to examine the effects of NIFED or ISO treatment in the presence of specific directions of stretch.…”
Section: Iso At 1ϫ10mentioning
confidence: 99%
“…Cardiac remodeling resulting from increased heart rate and hemodynamic overload, or increased workload and increased wall tension (Lijnen et al 2000;Ozaki et al 2002) initiates cardiac hypertrophy as evidenced by both in vivo (Benjamin et al 1989;Zierhut and Zimmer 1989;Boluyt et al 1995) and in vitro (Clark et al 1991;Zou et al 1999) studies. Chronic stimulation of β-adrenergic receptor associated with cardiac overload and congestive heart failure (Bristow 2000) may cause progressive myocyte dysfunction, cell loss or cardiac chamber remodeling (Limbird and Voughan 1999) as it has been demonstrated in humans and experimental animals.…”
Section: Introductionmentioning
confidence: 99%